Comparative investigations in the U.S. IBP grassland biome, decomposition section - Coleman, David C., 1938-, author; Natural Resource Ecology Laboratory, Colorado State University, publisher (Colorado State University. Libraries, 1973)
Paper presented at the Minneapolis, Minnesota Meeting of the Ecological Society of America/AIBS Meetings, August 28, 1972.
March, 1973.
On cover: Grassland Biome, Ecosystem analysis studies, U.S. International Biological Program.
Keywords: Soil ecology; Biodegradation